Efecto de cuatro purines de origen botánico, en la descomposición de abonaduras orgánicas mediante sistema de aboneras mejoradas - Solano Naranjo, Jenifer Noemí (2015)
The development of organic fertilizers take a very important place in agriculture, as it contributes to the improvement of structures and soil fertility through the incorporation of nutrients, microorganisms, and also regulating soil pH. With the use of organic fertilizers farmers can reduce the use of external inputs and increase the efficiency of community resources, while protecting human health and the environment. The objective of this research was to evaluate the effect of four purines botanicals in the decomposition of organic abonaduras by system improved fertilizers, further economic analysis. The work was done on the grounds of the experimental farm of the Faculty of Agricultural Sciences at the Technical University of Babahoyo, located at Km. 7.5 of the Babahoyo-Montalvo route. Eleven treatments and three replicates were investigated. Plots of 1 m2 was used. The treatments were arranged in a completely randomized design blocks. Tukey test at 5% significance was used for the assessment of means. Chemical analysis of slurry was performed, the temperature of organic waste was evaluated for 8 days, material moisture, pH of the compost, organic matter decomposition time, yield compost and microbial analysis.